Carbon sequestration and land rehabilitation through Jatropha curcas (L.) plantation in degraded lands - Wani, S.P.; Chander, G.; Sahrawat, Kanwar Lal; Srinivasa Rao C; Raghvendra G; Susanna P; Pavani M (Elsevier, 2012)
The effects of growing Jatropha in on-farm and on-station degraded lands were evaluated on carbon (C) sequestration and soil properties. Jatropha accumulated and added to soil significant amounts of C (305 kg ha−1 year−1) from the year one itself. Overall, a 3–5-year old plantation added per year around 4000 kg plant biomass equivalent to 1450 kg C ha−1 – 800 kg C through leaves, 150 kg C through pruned twigs, and 495 kg C as deoiled Jatropha cake. Biodiesel C replacement in the fossil fuel was 230 kg ha−1. Besides adding biomass to the soil, and C replacement in fossil fuel; the standing Jatropha rendered ecosystem service by fixing 5100–6100 kg ha−1 C as the aboveground plus belowground biomass. Carbon additions by Jatropha during 4 years increased C content in the degraded surface soil layer by 19%, resulting in about 2500 kg ha−1 C sequestered. Huge C additions and live root activity under Jatropha increased microbial population, respiration rate and microbial biomass C and N in soil. Along with C additions, 4000 kg ha−1 year−1 plant biomass recycled into the soil 85.5 kg nitrogen, 7.67 kg phosphorus, 43.9 kg potassium, 5.20 kg sulphur, 0.11 kg boron, 0.12 kg zinc and other nutrients. The C additions improved water holding capacity of the soil under Jatropha as compared with the adjacent control soil which increased by 35% at 30 kPa and 21% at 1500 kPa soil water potential.